Evaluation of Vibrio parahaemolyticus Immersion Conditions for Infection Establishment and Conventional PCR Detection in Vaname Shrimp (Litopenaeus vannamei): A Preliminary Study: Evaluation of Vibrio parahaemolyticus Immersion Conditions for Infection Establishment and Conventional PCR Detection in Vaname Shrimp (Litopenaeus vannamei): A Preliminary Study - Richen Stella Purba; Yuni Kilawati; Muhammad Fakhri; Kurrotul Uyun; Aditya Ragil Suharto (Department of Aquaculture, 2026)
The Pacific white shrimp (Litopenaeus vannamei) is an important aquaculture commodity, but it is highly susceptible to Acute Hepatopancreatic Necrosis Disease (AHPND) caused by Vibrio parahaemolyticus. Experimental infection models are needed to support molecular detection; however, information regarding the optimal incubation period for successful infection remains limited. This study aims to evaluate the effect of immersion duration and bacterial concentration of V. parahaemolyticus on infection establishment and conventional PCR detectability in a preliminary laboratory-scale challenge test. A laboratory experimental design was employed using seven infection treatments and one negative control, varying bacterial concentration (10⁶–10⁹ CFU/mL), immersion duration, and post-immersion conditions. Shrimp were infected using the immersion method, followed by hepatopancreas sampling for DNA extraction and PirA gene detection via PCR. PCR results were evaluated qualitatively based on the presence of specific amplification bands and PirA concentration. Results showed that shrimp immersed at a concentration of 10⁶ CFU/mL for 24 hours (A1) may represent a promising condition for achieving detectable conventional PCR amplification of the pirA gene while maintaining high shrimp survival. These results indicate that both immersion duration and bacterial concentration may influence the balance between detectable infection and host viability, providing preliminary insight for the development of a sublethal infection model of V. parahaemolyticus in L. vannamei under laboratory-scale conditions. This condition may serve as a practical reference for future experimental infection studies and for the evaluation of preventive or therapeutic strategies against AHPND in shrimp aquaculture.